2012
DOI: 10.1002/rcm.6282
|View full text |Cite
|
Sign up to set email alerts
|

The role of conformational flexibility in β2‐microglobulin amyloid fibril formation at neutral pH

Abstract: RATIONALE Amyloid formation is implicated in a number of human diseases. β2-microglobulin (β2m) is the precursor protein in dialysis-related amyloidosis and it has been shown that partial, or more complete, unfolding is key to amyloid fibril formation in this pathology. Here the relationship between conformational flexibility and β2m amyloid formation at physiological pH has been investigated.METHODS HDX-ESI-MS was used to study the conformational dynamics of β2m. Protein engineering, or the addition of Cu2+ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 53 publications
(194 reference statements)
0
23
0
1
Order By: Relevance
“…By massively increasing its interest in protein therapeutics within these last years, the biopharmaceutical industry became particularly interested in improving and developing spatially resolved analytical techniques like HDX-MS for its needs in both research and quality control. (14,15) Since so far HDX-MS was mostly implemented on monomeric proteins (16)(17)(18)(19)(20)(21)(22) and only a few studies have been conducted on homo-oligomeric proteins (23)(24)(25)(26)(27) or protein complexes, (28)(29)(30)(31) efforts have to be continued for extracting the dynamic determinants of complexes.…”
Section: Introductionmentioning
confidence: 99%
“…By massively increasing its interest in protein therapeutics within these last years, the biopharmaceutical industry became particularly interested in improving and developing spatially resolved analytical techniques like HDX-MS for its needs in both research and quality control. (14,15) Since so far HDX-MS was mostly implemented on monomeric proteins (16)(17)(18)(19)(20)(21)(22) and only a few studies have been conducted on homo-oligomeric proteins (23)(24)(25)(26)(27) or protein complexes, (28)(29)(30)(31) efforts have to be continued for extracting the dynamic determinants of complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite truncation of the N-terminal six residues, ΔN6 displays only minor structural differences compared with hβ 2 m in the native form (25). Although the structural properties of ΔN6 cannot explain its enhanced ability to form amyloid fibrils at neutral pH, increased conformational dynamics evidenced by NMR relaxation times ( T 2 values) (25), hydrogen exchange protection (2729), molecular dynamics simulations (30), and denaturation with guanidinium chloride (GuHCl) (31) have been linked to its ability to form fibrils at this pH.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, experiments in vitro have shown that amyloid fibrils will not form in physiological conditions (of pH and temperature) even when the concentration of Hβ 2 m largely exceeds that observed in DRA patients [5,6]. Although it is widely recognized that WT Hβ 2 m is unable to efficiently nucleate fibrillogenesis in vitro under physiological conditions, it is also known that a multitude of environmental factors (e.g., acidic pH [7], agitation [8], addition of Cu 2+ in the presence of urea [9], co-solvents [10]), can trigger the formation of β 2 m amyloid fibrils in laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%